A Bidirectional Heuristic Search for web service composition with costs. (1st July 2010) - Ukey, Nilesh; Niyogi, Rajdeep; Singh, Kuldip; Milani, Alfredo; , Valentina Poggioni
This paper presents a model for web service composition based on navigating the web service dependency graph by bidirectional heuristic algorithm. The algorithm is based on a new domain-independent heuristic, while a cost optimisation strategy that balances optimality and convergence performance is also proposed. Experiments on different types of dependency graphs of varying sizes and number of web services show promising results for the service composition model when compared with state-of-the-art search algorithms. The proposed dependency-graph-based composition model can be extended to more general frameworks such as collective systems and virtual environments where a plurality of agents interact composing different actions, services, or resources.